The relationship between service quality and memorable tourism experience at Giant Panda Conservation Centre in Zoo Negara Malaysia - Thoo, Poh Yee; Johari, Shazali; Ismail, Mohd Hafizal; Yee, Lai Ling; Hasan, Muhammad Luqman (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Service quality has always been the highlight in service-based sectors especially in the tourism sector where experience is their primary product. However, to be successful in this highly competitive tourism industry, bestowing visitors with great service quality and increase their positive memorable tourism experiences (MTEs) are essential as satisfaction alone is proven to be insufficient. Zoo Negara is the oldest zoo in Malaysia, but it is one of the latest additions to the panda zoo around the world as it has been chosen to house a pair of giant pandas named Fu Wa (Xing Xing) and Feng Yi (Liang Liang) for 10 years. Therefore, this exploratory research examines whether service quality is an antecedent of MTEs for GPCC in Zoo Negara Malaysia. Many studies have been done at GPCC but none have linked service quality with the MTEs in their studies. This study seeks to increase their understanding of their service quality and MTEs, and nevertheless covers the gap between the two dimensions for zoo setting. Quantitative method has been used, and a purposive sampling approach has been employed. The data gathered were analysed using multiple regression analysis. Results indicated that service quality is an antecedent of MTEs where both technical quality and functional quality have positive relationship with MTEs. This has bridged the gap for current literature. Hence, it is necessary for the management of Zoo Negara to enhance their service quality of GPCC so that more people will have positive MTEs that will eventually increase the possibility of a person to revisit it.